The Evaluation of Diastolic Dysfunction with Tissue Doppler Echocardiography in Women with Subclinical Hypothyroidism and the Effect of L-Thyroxine Treatment on Diastolic Dysfunction: A Pilot Study. (8th August 2011) - Erkan, Gulbanu; Erkan, Aycan Fahri; Cemri, Mustafa; Karaahmetoglu, Selma; Cesur, Mustafa; Cengel, Atiye
Abstract : Background . Subclinical hypothyroidism (SH) predominantly affects women. The necessity of treatment in SH is controversial. Objective . We aimed to investigate the response of diastolic dysfunction to thyroid hormone replacement therapy (THRT) in women. Methods and Results . Twenty-two female subjects with SH and 20 euthyroid female controls were enrolled. Baseline and follow-up biochemical, hormonal, and echocardiographic evaluations were performed. Repeat echocardiograms were performed three months after the achievement of a euthyroid status with THRT. Mean baseline myocardial performance index (MPI) was0.27 ± 0.08 in the SH group, and0.22 ± 0.06 in the control group (P = 0.03 ). MPI did not change significantly after THRT. Pulsed-wave Doppler findings were not different among the groups. However, tissue Doppler-derived mitral annular E' velocities were significantly lower in the SH group. A moderate but significant improvement was observed in E' velocities after THRT (13.2 ± 3.87 versus14.53 ± 2.75, P = 0.04 ). We also observed left ventricular concentric remodeling in SH patients which was reversible with THRT. Conclusions . Tissue Doppler echocardiography may be a useful tool for monitoring the response of diastolic dysfunction to thyroid hormone replacement therapy in patients with SH. Our findings suggest that THRT may reverse diastolic dysfunction in women with SH.